Hidrocefalia canina : reporte de casos (2001)
ABSTRACT: Hydrocephalus is a pathologic enlargement of the ventricular system secondary to an increased volumen of cerebrospinal fluid (CSF). This disease can be acquired or congenital. The clinical signs vary from total absence of manifestation to alteration of mental status. The medical and/or treatments could stabilize these patients, but their prognosis continuos to be guarded to poor. This article presents an overhaul of aspects of the pathophysiology, diagnostic plan and treatment of congenital hydrocephalus and three clinical cases that arrived the Veterinary Teaching Clinic of University of Antioquia, which presented as a definitive diagnose congenital hydrocephalus, each one with a myriad of clinical signs.